“Lots of doctoring, with great success”: Healthcare within the Port Royal Experiment and the Work of Laura M. Towne - Antje Dallmann (European Journal of American Studies)
In 1862, Laura M. Towne – abolitionist, teacher, educator, and trained homeopath – joined the Port Royal Experiment, a project initiated by Northern benevolent societies to provide education and relief for former slaves on the South Carolina Sea Islands, which had been occupied by Union troops in late 1861. On the Sea Islands as well as in broader Northern culture, healthcare for freedpeople – and freedpeople’s health – soon became controversial topics. This article traces how Towne as homeopathic practitioner uses medical tropes in autobiographic documents intended for publication or circulation in the North to increase her own authority within a wartime discourse and how, at the same time, she avoids reflection about medical crises.